Doping of Ga2O3 bulk crystals and NWs by ion implantation - Lorenz, K. (2014)
Ga2O3 bulk single crystals have been implanted with 300 keV Europium ions to fluences ranging from 1x10(13) to 4x10(15) at/cm(2). The damage build-up and Eu-incorporation was assessed by Rutherford Backscattering Spectrometry in the channeling mode (RBS/C). RBS/C results suggest that implantation causes a mixture of defect clusters and extended defects such as dislocations. Amorphisation starts at the surface for fluences around 1x10(15) at/cm(2) and then proceeds to deeper regions of the sample with increasing fluence. Amorphous regions and defect clusters are efficiently removed during rapid thermal annealing at similar to 1100 degrees C; however, Eu diffuses towards the surface. Nevertheless, Eu ions are optically activated and show cathodoluminescence at room temperature. Results in bulk samples are compared to those in Eu-implanted Ga2O3 nanowires and despite strong similarities in the structural properties differences were found in the optical activation. Furthermore, damage and dopant incorporation studies were performed using the Perturbed Angular Correlation technique, which allows probing the immediate lattice surroundings of an implanted radioactive probe at the atomic level.